Designing Software Quality Assurance Framework Integrated With Scrum And Rsm For Multi-Project - Devi Veronica; Muharman Lubis; Basuki Rahmad (Yayasan Vifada Cendikia Indonesia, 2026)
Purpose: This study aims to design an integrated Software Quality Assurance (SQA) framework combining Scrum and the Recognize, Scrutinize, Materialize (RSM) approach to mitigate context switching, priority ambiguity, and technical debt in multi-project environments. Research Design and Methodology: Utilizing a mixed-methods approach with sequential triangulation based on Design Science Research (DSR), secondary data were gathered from SOP studies at PT. Boer Technology. Framework evaluation involved a 1–5 Likert-scale questionnaire administered to a purposive sample of 9 active expert Scrum Masters Findings and Discussion: Descriptive statistics and inter-rater reliability analysis confirm a high expert consensus, with a 99.02% cumulative positive response rate. Gwet’s AC2 yielded a fair agreement of 0.2279, demonstrating that integrating RSM strengthens shift-left testing and continuous quality execution without compromising Scrum's iterative nature Implications: This framework offers an original, implementable quality governance solution for medium-to-large software industries to enhance compliance, product stability, and business value. Future research should conduct empirical pilot implementations to test scalability and quantitatively measure long-term impacts using metrics like defect density